The Sexual Minority Rights Conundrum in Africa: Contextualising the Debate Following the Coalition of African Lesbians’ Application for Observer Status Before the African Commission - Osogo Ambani, John (Strathmore Law Journal, 2016)
Although the African human rights legal system boasts of many treaties, the most relevant in the context of sexual minority rights is the African Charter on Human and Peoples’ Rights (African Charter), which agreement enjoys near unanimous ratification by members of the African Union (AU). As Vincent Nmehielle justly noted, ‘the African Charter is the primary normative instrument of the African human rights system.’ It thus may easily be regarded as the ‘regional bill of rights.’ This paper will deal with this matters, showing the status questionis in Africa.